Securing Debt in the Knowledge Economy: Evidence from Intellectual Property Registers - Ciaramella, Laurie; Heller, David; Leitzinger, Leo (Journal of Financial and Quantitative Analysis, 2026)
An abstract is not available for this content so a preview has been provided. Please use the Get access link above for information on how to access this content.